1995
DOI: 10.1111/j.1600-0587.1995.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐dwelling spiders (Arachnida, Araneae) in fragmented old forests and surrounding managed forests in southern Finland

Abstract: We studied the structure of spider assemblages in fragments of old coniferous forest in the southern Finnish taiga We sampled spiders with pitfall traps in the interiors and in the edges of the old‐forest patches and in the surrounding managed forests We surveyed assemblages of ground‐dwelling spiders and the relation of species to formerly mentioned three forest‐habitat categories We analysed spider assemblages in relation to vegetation structure as well As in forest spiders there are no habitat specialists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
152
0
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(163 citation statements)
references
References 19 publications
8
152
0
3
Order By: Relevance
“…These stands exhibited high spider species richness and open habitat species richness as well as low dominance (as found by Pajunen et al, 1995) as well as the greatest cover of lower field layer vegetation. The vegetation of the pre-thicket plots was dominated by species typical of open habitats and was generally taller, and probably more structurally diverse, than in the more mature plots.…”
Section: Pre-thicket Standsmentioning
confidence: 99%
“…These stands exhibited high spider species richness and open habitat species richness as well as low dominance (as found by Pajunen et al, 1995) as well as the greatest cover of lower field layer vegetation. The vegetation of the pre-thicket plots was dominated by species typical of open habitats and was generally taller, and probably more structurally diverse, than in the more mature plots.…”
Section: Pre-thicket Standsmentioning
confidence: 99%
“…2F-J ; Davies & Margules, 1998 ;Kotze & Samways, 1999Bolger et al, 2000). In a study of spider communities in forest fragments in Finland, it was shown that large hunting spiders were most abundant near forest edges where the environment was warmer, more open, and the leaf litter layer was thick enough to allow stratification of adults and juveniles, which reduced the probability of cannibalism (Pajunen et al, 1995). By contrast, in the same forest fragments, small web-building spiders were more likely to inhabit the forest interior, where the herb and moss cover provided suitable microhabitat structures for web construction (Pajunen et al, 1995).…”
Section: Edge Effects (1 ) Community Composition At Habitat Bounmentioning
confidence: 99%
“…Ha tájléptékű diverzitást vizsgálunk, akkor a fajszám-élőhelyméret összefüggés az egyik legfontosabb ökológiai elmélet (Lawton 1999). Miyashita et al (1998) a habitat mérete és a pókközösségek fajszáma közt pozitív korrelációt, Hopkins és Webb (1984), Webb és Hopkins (1984) negatív kapcsolatot mutatott ki, mert a környező foltok populációi növekvő arányban bejutnak az élőhelyre (Usher et al 1993), Pajunen et al (1995), Bonte et al (2002), Gibb és Hochuli (2002) nem talált összefüggést. Pearce et al (2005) vizsgálata szerint a kis foltokban alacsonyabb a fajszám és az egyedszám, mert a növekvő mérettel növekedik a mikrohabitatok száma/változatossága a folton belül.…”
Section: Tájléptékű Váltózók Hatása a Pókközösségekreunclassified
“…Hopkins és , Webb és Hopkins (1984) negatív kapcsolatot talált a habitat mérete és a fajszám közt, számos szerző vizsgálata alapján nincs köztük összefüggés (Pajunen et al 1995, Bolger et al 2000, Bonte et al 2002, Gibb és Hochuli 2002, Pearce et al 2005, Miyashita et al (1998) Az egyes élőhelyfoltok közti "mátrix‖ kevésbé veszélyes az elsősorban az élőhely-szigetekre jellemző fajok számára, mint a valódi szigetek esetén, itt hosszabb ideig túlélhetnek, és valószínűleg nagyobb távolságokat tehetnek meg . A fülöpházi vizsgálat során is gyűjtöttünk erdei fajokat a nyílt homoki gyepen (pl.…”
Section: Az éLőhelyfoltok Méretének Hatásaunclassified
See 1 more Smart Citation